Time-Restricted Feeding in Commercial Layer Chickens Improves Egg Quality in Old Age and Points to Lack of Adipostat Activity in Chickens - Saibaba, Ganesan; Ruzal, Mark; Shinder, Dima; Yosefi, Sara; Druyan, Shelly; Arazi, Hagit; Froy, Oren; Sagi, Dror; Friedman-Einat, Miriam (Frontiers in Physiology, 2021)
In mammals, time-restricted feeding (TRF( with no caloric restriction provides health benefits and extends longevity, usually with a minor (~3%) or no reduction in total food consumption. In the current study, a TRF regimen of 6h free access to food (08:00 to 14:00h) was applied to Leghorn chickens from 25 to 86 weeks of age; control birds ate freely during the light hours (06:00 to 20:00h). Unexpectedly, the TRF-treated birds consumed, on average, 11.7% less food than the controls. This was manifested by an average reduction of of 9.6% in body-weight, 2.6-fold in visceral fat accumulation and 6.5% in egg-weight. Hen-housed egg production was reduced by 3.6% in the TRF group compared to the control, along the first 40 weeks of the follow-up (P<0.05) and changed into a tendency of 0.7% higher egg production thereafter. Several parameters of egg quality, showed significant improvement (P<0.05) in the TRF group compared to controls. A comparison of diurnal patterns of feed consumption revealed a higher rate of hourly consumption in the TRF group and increased consumption before dark in the control group. In conclusion, the reduced feed intake in response to the TRF treatment loss in visceral-fat accumulation supports the lack of a strong adipostat activity in chickens and different appetite-regulation mechanisms compared to mammals. Therefore, future TRF studies in chickens should be adjusted by extending the ad libitum time window. The lower feed intake by the TRF treated chickens compared to the ad libitum fed controls, seems to reduce efficiency of egg production. Nevertheless, the improved egg quality and persistence of egg lay at the older age, suggests that similarly to mammals, the TRF treatment delayed at least some of the negative impacts associated with advanced age.